EFEKTIVITAS QARDH AL-HASAN DALAM KERANGKA ZAKAT PRODUKTIF UNTUK PEMBERDAYAAN UMKM - Fauzi Rizal (Universitas Muhammadiyah Prof Dr Hamka, 2022)
Diversity in living conditions Is an inevitability in this world and poverty is a serious problem that must be solved. Criminality and the tragedy of theft cannot be separated from the problem of poverty. In the midst of this problem, zakat is a solutive step to solve the problem of economic inequality in the midst of the community. In addition to zakat as a command from Allah SWT, it is also a